A Citrus and Pomegranate Complex Reduces Methylglyoxal in Healthy Elderly Subjects: Secondary Analysis of a Double-Blind Randomized Cross-Over Clinical Trial - Bednarska, Katarzyna; Fecka, Izabela; Scheijen, Jean L. J. M.; Ahles, Sanne; Vangrieken, Philippe; Schalkwijk, Casper G. (International journal of molecular sciences, 2023)
Reactive α-dicarbonyls (α-DCs), such as methylglyoxal (MGO), glyoxal (GO), and 3-deoxyglucosone (3-DG), are potent precursors in the formation of advanced glycation end products (AGEs). In particular, MGO and MGO-derived AGEs are thought to be involved in the development of vascular complications in diabetes. Experimental studies showed that citrus and pomegranate polyphenols can scavenge α-DCs. Therefore, the aim of this study was to evaluate the effect of a citrus and pomegranate complex (CPC) on the α-DCs plasma levels in a double-blind, placebo-controlled cross-over trial, where thirty-six elderly subjects were enrolled. They received either 500 mg of Citrus sinensis peel extract and 200 mg of Punica granatum concentrate in CPC capsules or placebo capsules for 4 weeks, with a 4-week washout period in between. For the determination of α-DCs concentrations, liquid chromatography tandem mass spectrometry was used. Following four weeks of CPC supplementation, plasma levels of MGO decreased by 9.8% (−18.7 nmol/L; 95% CI: −36.7, −0.7 nmol/L; p = 0.042). Our findings suggest that CPC supplementation may represent a promising strategy for mitigating the conditions associated with MGO involvement. This study was registered on clinicaltrials.gov as NCT03781999.